A computational model for transport in partially ergodized magnetic fields - Reiter, D.; Runov, A.; Kasilov, S. (Вопросы атомной науки и техники, 2000)
A 3-dimensional plasma uid transport problem for fusion edge plasmas is considered. Conventional numerical methods from uid dynamics or gas dynamics are not applicable, if the coordinate line along one of the main transport directions exhibits ergodic behaviour at least in some regions of the computational domain. In stellarator plasma edges, or in tokamaks with eld line perturbations as foreseen for TEXTOR under dynamic ergodic divertor (DED) operation, such complications can arise. We propose and discuss a novel "Multi-Coordinate System Approach" within the framework of a Monte Carlo procedure. A 3-dimensional plasma uid code is developed, benchmarked and applied to a model with geometrical and magnetic eld parameters chosen to fall in the range of parameters expected for TEXTOR with DED [1]. The resulting patterns in the computed plasma temperature eld near the perturbation coils are in accordance with experimental observations of the radial modulation of the temperature eld in TORE SUPRA, though under slightly di erent experimental conditions there.